Dignity entitlements contra property rights: are all preferences reducible to a single metric? - Elias L. Khalil (20518877) (2023)
Standard rational choice theory assumes away any difference between goods: a box of tomatoes (or its opposite, rotten tomatoes) is treated in the same way as esteem (or its opposite, indignity), as both can be reduced to a single-metric function (benefit). Such treatment of all goods and, corollary, preferences as comparable, i.e. as belonging to a single-metric function, has been questioned by non-economists, moral philosophers, and non-standard economists such as Amartya Sen. Indeed, the supposed comparability of goods/preferences thesis does not correspond to how legal systems work. Legal systems protect property ownership of substantive goods such as tomatoes—against theft (criminal law) and against (the focus of this paper) reneging on contracts (civil law). In contrast, legal systems usually do not protect dignity or what can be called ‘dignity entitlements’ regarding esteem. Does this asymmetry pose a challenge to standard rational choice theory? Not necessarily. It could be the case that legal systems should protect dignity entitlements as they protect property rights. To answer the question, this paper compares two games with only one difference that can only be traced back to the hypothesized difference between substantive and esteem preferences. The comparison of the Nash equilibria finds that the two games challenge standard rational choice: this finding supports the proposed substantive/esteem incomparability thesis. Of more importance, this finding generally vindicates legal systems that more-or-less ignore dignity entitlements, i.e. do not protect them as they protect property rights. Other Information Published in: Cogent Social Sciences License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://doi.org/10.1080/23311886.2024.2371492